Smith 1. Lisa Wilson interviews Pat and Lloyd Smith, Heart's Content. - Wilson, Lisa (2012)
Lisa Wilson interviews Pat and Lloyd Smith regarding living in the Heart's Content heritage district, part 1, Heart's Content.